Critical Thinking Disposition and Independent Learning of Teacher Candidates in Online Learning for Geometry Materials - Ari Suningsih; Dwi Juniati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
This study aims to look at the effect of independent learning on mathematics learning achievement, 2) the effect of critical thinking disposition on mathematics learning achievement, and 3) the effect of joint learning independence and critical thinking disposition on mathematics learning achievement during online lectures for the Analytical Geometry course. flat 4th semester students of Mathematics Education Study Program, FKIP UMPRI. This type of research is quantitative using an ex post facto approach. The research population amounted to 27 people. Data analysis technique using multiple linear regression. The findings of the research are: 1) There is an influence of independent learning on the achievement of 4th semester students of the Mathematics Education Study Program FKIP UMPRI in online lectures for the Basic Analytical Geometry course. 2) There is an influence of critical thinking disposition on the achievement of first semester students of Mathematics Education Study Program FKIP UMPRI in online lectures for the Field Analytical Geometry course. 3) There is an effect of learning independence and critical thinking disposition together on student achievement in online lectures for the Field Analytical Geometry course. From the results of R Square = 0.669 x 100% = 66.9% which shows that student achievement in online lectures is for the eye Field Analytical Geometry course can be explained by independent learning and critical thinking disposition of 66.9%.